Post-stroke fatigue: a problem of altered corticomotor control?. Issue 8 (17th April 2015) - Kuppuswamy, A; Clark, E V; Sandhu, K S; Rothwell, J C; Ward, N S
Abstract : Objectives: We recently showed that diminished motor cortical excitability is associated with high levels of post-stroke fatigue. Motor cortex excitability impacts movement parameters such as reaction and movement times. We predicted that one or both would be influenced by the presence of post-stroke fatigue. Methods: 41 first-time stroke survivors (high fatigue n=21, Fatigue Severity Scale 7 (FSS-7) score >5; low fatigue n=20, FSS-7 score <3) participated in the study. Movement times, choice and simple reaction times were measured in all participants. Results: A three way ANOVA with fatigue (high and low), task (movement time, simple reaction time and choice reaction time) and hand (affected and unaffected) as the three factors, revealed a significant difference between affected (but not unaffected) hand movement times in the high compared to low fatigue groups. Reaction times, however, were not different between the high-fatigue and low-fatigue groups in either the affected or unaffected hand. Conclusions: Previously, we showed that motor cortex excitability is lower in patients with high post-stroke fatigue. Our current findings suggest that post-stroke fatigue (1) is a problem of movement speed (possibly a consequence of diminished motor cortex excitability) and not movement preparation, and (2) may have a focal origin confined to the lesioned hemisphere. We suggest that low motor cortex excitability in the lesioned hemisphere is a viable therapeutic target in post-stroke fatigue.